Study of Homicidal Deaths Autopsied in VSSIMSAR, Burla: A Three-Year Retrospective Study - Dash , A; Xalxo , B; Panda , S; Perei , S (Journal of Indian Academy of Forensic Medicine, 2023)
Killing of an individual is the highest level of aggression found in society. Incidence of homicide is on the rise and its pattern is also changing with time. The present retrospective study was conducted in the department of Forensic Medicine and Toxicology, VIMSAR, st st Burla from 1 January 2018 to 31 December 2020. All the cases brought to the department for autopsy, either confirmed or later registered as homicide by investigating officer were considered for study. Among 4918 autopsies conducted during the period of 3 years 119 cases (2.41%) were of homicidal deaths. 66.4% of homicide victims are males. Majority of homicidal deaths occur in the age group 21-30 years and 31-40 years accounting for 52% of total cases combinedly. 46.2% homicide victims succumbed to injuries at the spot. Majority of cases (44 cases, 37%) occurred during night hours. Infliction of injuries are present in multiple areas in 42.8% of cases. Blunt weapons (29.4%) were the most commonly used. Defence wound were present in 19% of cases. Most common site of fatal injury is head in 46.2% of cases. In majority of cases (46.2%) cause of death was due to craniocerebral injury.